As mulheres e suas sesmarias : espacializações coloniais - Mato Grosso (1748 – 1799) - Silva, Ana Gomes da (2015)
This research deals with the policy of colonization and settlement of the west end of Portuguese colony in South America inaugurated by the governor and captain general Antonio Rolim de Moura Tavares and having continuity until the end of the 18th century, where the government of the military has been replaced by the administration of prefects. In the then, captaincy of Mato Grosso, created in the first half of the 18th century occurred the Portuguese specialization (enlargement of borders), and repossession of the population group with the dispossession of Amerindian peoples. The set of documents researched concerns specifically the letters sesmarias granted women in the second half of the 18th century. In this sense, we question the settlement model used by the Portuguese, which realizes the deployment of medieval presúrias inserted into sesmarias law. With this legal adaptation women benefited from the Portuguese crown with the land grant which caused the women's empowerment in the land borders of conquest, conquest of metals and other people.